2021
DOI: 10.3389/fnut.2020.576966
|View full text |Cite
|
Sign up to set email alerts
|

The Milk Metabolome of Non-secretor and Lewis Negative Mothers

Abstract: Introduction: The functional role of milk for the developing neonate is an area of great interest, and a significant amount of research has been done. However, a lot of work remains to fully understand the complexities of milk, and the variations imposed through genetics. It has previously been shown that both secretor (Se) and Lewis blood type (Le) status impacts the human milk oligosaccharide (HMO) content of human milk. While some studies have compared the non-HMO milk metabolome of Se+ and Se− women, none … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 41 publications
1
22
0
Order By: Relevance
“…Among Americans and Europeans, indeed, 80% of the population express the secretor phenotype [ 33 ], making Group 4 extremely rare. In contrast, in some African populations, over ~38% are non-secretors, with higher probabilities of mothers belonging to Group 4 [ 39 ].…”
Section: Human Milk Oligosaccharides: Structure and Compositionmentioning
confidence: 99%
See 4 more Smart Citations
“…Among Americans and Europeans, indeed, 80% of the population express the secretor phenotype [ 33 ], making Group 4 extremely rare. In contrast, in some African populations, over ~38% are non-secretors, with higher probabilities of mothers belonging to Group 4 [ 39 ].…”
Section: Human Milk Oligosaccharides: Structure and Compositionmentioning
confidence: 99%
“…Different authors were able to differentiate breast milk on the basis of the secretor and non-secretor phenotype, regardless of the different metabolomics technology applied. Their studies demonstrated the abundance of α1-2 fucosylated HMOs (2′-FL, LNFP-I) in secretor’s milk and the absence of α1-2 fucosylated HMOs in non-secretor’s milk [ 39 , 40 , 123 , 126 , 127 , 133 ].…”
Section: Metabolomics and Human Milk Oligosaccaridesmentioning
confidence: 99%
See 3 more Smart Citations